Pernikahan Dini Sebagai Penghambat Pendidikan Remaja: Studi Kasus tentang Kondisi Psikologis dan Masa Depan Remaja di Kabupaten Brebes Jawa Tengah - Zulfasa Kaila Yuniasih; Azwa Qonitatun; Sahra Naura Luwistiana; Alifa Rizqi Kaila; Ratna Muthia (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2026)
This study analyzes the dynamics of "Early Marriage and Shattered School Hopes" regarding eroded psychological well-being and pawned adolescent ideals in Brebes Regency. Using a qualitative case study design, data were gathered via in-depth interviews, participatory observation, and document analysis from eight informants, processed using Miles and Huberman's interactive model. Findings reveal early marriage is not merely a social event but systemic trauma damaging psychological structures through three aspects: first, victims' psychological conditions marked by identity loss, prolonged anxiety, and "fatalistic resignation"; second, lost educational access due to interactions of "normative-cultural coercion," "institutional structural barriers," and "economic-domestic double burdens"; third, manifestations of buried ideals comprising "hindered academic grief," "identity cognitive conflict," and "internalized existential despair." The research proves education loss from early marriage destroys human potential, altering character, leaving spiritual voids, and perpetuating intergenerational poverty cycles, thus urgently demanding holistic interventions including psychosocial rehabilitation and alternative education pathways. This study's main contribution is introducing the "systemic trauma" concept that actively extinguishes adolescents' existential hopes, filling literature gaps by providing a detailed psychological map to formulate recovery policies previously neglected in early marriage prevention discussions.